2019
DOI: 10.3389/fnagi.2019.00343
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic Background Influences the Propagation of Tau Pathology in Transgenic Rodent Models of Tauopathy

Abstract: Alzheimer's disease (AD), the most common tauopathy, is an age-dependent, progressive neurodegenerative disease. Epidemiological studies implicate the role of genetic background in the onset and progression of AD. Despite mutations in familial AD, several risk factors have been implicated in sporadic AD, of which the onset is unknown. In AD, there is a sequential and hierarchical spread of tau pathology to other brain areas. Studies have strived to understand the factors that influence this characteristic spre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 38 publications
3
9
0
Order By: Relevance
“…A large number of pieces of evidence support a prion-like model for tau spreading, consisting of abnormal proteins with the capacity to convert normal proteins into a pathological form. The inoculation of brain extracts from mice or humans with tauopathy into the brain of wild-type animals induced tau pathology in recipient animals and its propagation from the site of injection along neuronal connections (Clavaguera et al, 2009 , 2013 ; Lasagna-Reeves et al, 2012 ; Ahmed et al, 2014 ; Guo et al, 2016 ; Gibbons et al, 2017 ; Narasimhan et al, 2017 ; Smolek et al, 2019a , b ). Similar results were obtained when synthetic tau fibrils were injected into young mice overexpressing mutant human tau (P301S) which resulted as well in the formation of NFT-like inclusions that propagated from the injected sites to connected brain regions in a time-dependent manner (Iba et al, 2013 ).…”
Section: The Spread Of Taumentioning
confidence: 99%
“…A large number of pieces of evidence support a prion-like model for tau spreading, consisting of abnormal proteins with the capacity to convert normal proteins into a pathological form. The inoculation of brain extracts from mice or humans with tauopathy into the brain of wild-type animals induced tau pathology in recipient animals and its propagation from the site of injection along neuronal connections (Clavaguera et al, 2009 , 2013 ; Lasagna-Reeves et al, 2012 ; Ahmed et al, 2014 ; Guo et al, 2016 ; Gibbons et al, 2017 ; Narasimhan et al, 2017 ; Smolek et al, 2019a , b ). Similar results were obtained when synthetic tau fibrils were injected into young mice overexpressing mutant human tau (P301S) which resulted as well in the formation of NFT-like inclusions that propagated from the injected sites to connected brain regions in a time-dependent manner (Iba et al, 2013 ).…”
Section: The Spread Of Taumentioning
confidence: 99%
“…Nevertheless, the increasing use of patient-derived brain lysates and the recent emergence of humanized tauopathy mouse models may be decisive in the search for a treatment capable of slowing disease progression or reversing its detrimental effects. Additionally, patient-derived tau seeding in rat models could also be further explored, as their larger brain size may make them better research models for characterizing tau PET tracers compared to mice [ 178 , 179 ]. Of note, robust cognitive deficits have thus far not been reported in seeding models.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that these abnormalities and aggregation of tau proteins are along with impairment in autophagy process (Ando et al, 2020). A newly published article has demonstrated that genetic background is a candidate involved in spread of tauopathy (Smolek et al, 2019). The aggregations of tau proteins are found in temporal, ventral, lateral, and primary cortical areas of brain.…”
Section: Tau Protein and Pathological Eventsmentioning
confidence: 99%